2019
DOI: 10.1136/bmjopen-2019-030201
|View full text |Cite
|
Sign up to set email alerts
|

Age-specific and sex-specific reference intervals for non-fasting lipids and apolipoproteins in 7260 healthy Chinese children and adolescents measured with an Olympus AU5400 analyser: a cross-sectional study

Abstract: AimsEthnic, demographic, lifestyle, genetic and environmental factors influence lipids and apolipoproteins. The aim of this study was to establish age-specific and gender-specific reference intervals for non-fasting lipids and apolipoproteins in healthy Chinese children and adolescents.MethodsThis study followed the Clinical and Laboratory Standards Institute EP28-A3c guidelines. Non-fasting samples were collected from 7260 healthy Chinese children and adolescents, and they were analysed using the Olympus AU54… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 34 publications
2
7
0
Order By: Relevance
“…The 95% CIs were calculated for each analyte and provided as a measure of the uncertainty of the RI estimation (Figures S3-S6 showed graphical representations of the estimated models of each analyte). A comparison between the indirect RIs in our cohort to those reported in the literature as direct measures in paediatric studies [20][21][22][23][24][25][26] is reported in Table S7. For all analytes except TG, the estimated RIs (both lower and upper limits) were in good agreement with those published.…”
Section: Resultsmentioning
confidence: 99%
“…The 95% CIs were calculated for each analyte and provided as a measure of the uncertainty of the RI estimation (Figures S3-S6 showed graphical representations of the estimated models of each analyte). A comparison between the indirect RIs in our cohort to those reported in the literature as direct measures in paediatric studies [20][21][22][23][24][25][26] is reported in Table S7. For all analytes except TG, the estimated RIs (both lower and upper limits) were in good agreement with those published.…”
Section: Resultsmentioning
confidence: 99%
“…In comparison with the study that was conducted in Birjand, a city in the east of Iran, LDL in both genders and TC in girls was higher compared to LDL and TC values in the current study, but HDL and TG were lower in the Birjand study compared to our study. Tese diferences between diferent regions of Iran may be due to dietary regimen, physical activity, hormonal status, environmental factors, and socioeconomic status, which can infuence the lipid profle in children [33,34] so that it is vital to provide age-and gender-specifc reference intervals using a local population [1].…”
Section: Discussionmentioning
confidence: 99%
“…Childhood dyslipidemia is considered a major worldwide health issue. Tis condition is positively correlated with a higher risk for cardiovascular disease (CVD), metabolic syndrome [1], and obesity [2], and when tracked into adulthood [3], consequently results in a higher rate of mortality [1].…”
Section: Introductionmentioning
confidence: 99%
“…Even from the perspective of a patient, it sets in ease and augment convenience for the laboratory services. 9,27 This may lead to more increased compliance from patients and could usher in newer future research to modify and better the norms improving the practice, thus making health care availability more convenient by rendering it more accessible and affordable.…”
Section: Discussionmentioning
confidence: 99%